Etnično razlikovanje v Sloveniji - Šumi, Irena (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2004)
The basic research project that the present article reports on carried in its title the formulation Ćprocesses of ethnic differentiation in SloveniaĆ ratherthan a more positivistic expression, for example Ćethnic groups in Slovenia.Ć The distinction between the statements Ćvarious ethnic groups live in SloveniaĆ and Ćprocesses of ethnic differentiation take place in SloveniaĆ is crucial: what intervenes between the two is precisely the reorganisation ofperspective, that is, shift in the point of view, that distinguished betweeneveryday, commonsensical perception of reality and its analytical deconstruction. On the level of everyday life, both perceptions are obviously and verifiably true: the difference being that the former does not have analytical potential, whereas the latter does. This confines the first statement to the realm of so-called commonsensical, popular conception, while the second one situates itself in the realm of scientific analysis. The main problem in the Slovenian context is that the difference between the above types of perceptions is not clearly recognized in any public discourse - professional, political, and media - and that the statements are read as equivalent. The author uncovers the characteristics of the processes of ethnicdifferentiation in Slovenia with examples from expert production, history writing, political, legal and media discourses.
Keywords: Slovenia; Slovenija; etnične skupine; etnični odnosi